Digital Revolution in Spatial Planning: The Potential of Geolocation Data in Czechia - Petr Jirásek; Radovan Šomplák (Urban Science)
This article analyzes population movement patterns in the Vysočina Region, Czechia, using mobile network geolocation data. Geolocation data provide new insights into population movement and structure, capturing real-time fluctuations in population size at different times of day and days of the week. The article aims to contribute to a better understanding of spatiotemporal population dynamics and identify links between movement patterns and different types of areas. Key mobility trends, such as work commuting, seasonal migration related to second homes and tourism, and the influence of urbanization on movement patterns, are identified. A scaling approach for categorizing municipalities based on their characteristics is proposed and tested in a case study of Vysočina Region municipalities. Furthermore, a case study of various municipality types demonstrates the practical application of geolocation data in spatial planning. The results highlight the value of these data for spatial planning, enabling a better understanding of population needs and optimization of public services and infrastructure.